WEB BASED ONLINE SHOP DESIGN SYSTEM AT AR SHOP - Ulfa Arma; Muhammad Yusril Pratama; Putri Afifah; Khusnul Khotimah (Sienna, 2023)
An online store website facilitates both buyers and sellers to view products anytime and anywhere, while allowing sellers to easily promote their items to a wide audience. The lack of effective product promotion has resulted in a decrease in the store's revenue and manual inventory management. The purpose of this research is to enhance sales at AR Store and assist in checking product inventory to streamline and expedite services at AR Store. The Waterfall method is employed, which involves the following steps: Analysis, Design, Coding, and Testing. The system is designed using programming languages such as HTML, CSS, and PHP. This research yields an online store website that provides information about products and available stock.